Mathematical model of the ultrahigh-frequency device with virtual cathode - Kravchenko, Yu. S.; Melnychuk, O. M. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Mathematical model of vircator is developed. The model serves as the basis for calculation of principle output characteristics of the device. Graphic results are obtained. By means of the program environment of calculation MatLab 6.1 it is shown, that at frequency of generation 18 GHz the value of efficiency factor is 9 %, and with increase of generation frequency , the full efficiency factor of vircator non linearly decreases, that is connected with complications while reorganization of generation frequency with its increase.